2015
DOI: 10.1097/md.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Amyotrophic Lateral Sclerosis in a Patient With Klippel–Feil Syndrome—a Familial Occurrence

Abstract: The rationale for this article is a description of a unique, familial case of a patient with amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disorder of unknown etiology coexisting with Klippel–Feil syndrome (KFS), a congenital malformation of cervical vertebrae, characterized by a fusion of minimum 2 cervical vertebrae.We report a 68-year-old man with moderate dysarthria, fasciculations, short neck, hearing deficit, and low posterior hairline. Definite ALS was diagnosed based on neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Pathway analysis revealed a remarkable loss of TGFβ pathway activity in oligodendrocytes from ALS patients, suggesting a pathogenic role for loss of TGFβ pathway activity in this disease. This finding is in full agreement with reports describing loss-of-function mutations in the ZNF512B gene that result in loss of TGFβ pathway activity and are associated with susceptibility to, and more aggressive, ALS 68,69 . Recently, an elegant mouse model revealed that loss of TGFβ pathway activity in glia cells causes demyelinating diseases 70 .…”
Section: Discussionsupporting
confidence: 92%
“…Pathway analysis revealed a remarkable loss of TGFβ pathway activity in oligodendrocytes from ALS patients, suggesting a pathogenic role for loss of TGFβ pathway activity in this disease. This finding is in full agreement with reports describing loss-of-function mutations in the ZNF512B gene that result in loss of TGFβ pathway activity and are associated with susceptibility to, and more aggressive, ALS 68,69 . Recently, an elegant mouse model revealed that loss of TGFβ pathway activity in glia cells causes demyelinating diseases 70 .…”
Section: Discussionsupporting
confidence: 92%
“…Clinical signs of the upper and lower motor neuron deficits in the cervical, thoracic, and lumbar regions supported by the results of electrophysiological and biochemical testing led to a diagnosis of ALS. 15 Therefore, it can be concluded that this is a very rare combination. Taking into account the fact that hydromyelia is a phenotypic feature of some neurodegenerative diseases, 8,9 there is a possibility that hydromyelia may be a part of the phenotype in the rare cases of ALS.…”
Section: Discussionmentioning
confidence: 95%
“…After a diagnostic work‐up the cervical syringomyelia was excluded as the cause of the symptoms observed in the patient. Clinical signs of the upper and lower motor neuron deficits in the cervical, thoracic, and lumbar regions supported by the results of electrophysiological and biochemical testing led to a diagnosis of ALS 15 …”
Section: Discussionmentioning
confidence: 98%
“…Authors of one study including nine MS patients with syringomyelia concluded that syringomyelia was not a coincidental finding but likely associated with MS pathophysiology, considering the low prevalence of syringomyelia in the normal population [ 24 ]. Syringomyelia was also recently reported in patients with amyotrophic lateral sclerosis (ALS) [ 25 26 ], while a study using MRI data to study CSF dynamics revealed different CSF hydrodynamics in ALS patients compared to healthy controls [ 27 ]. The mechanism behind syrinx formation in these patients is uncertain at this point, but drawing these findings together, one could hypothesize that the neurodegenerative change in nerve tissue might alter normal CSF drainage from the central canal.…”
Section: Discussionmentioning
confidence: 98%